The study on pyrolysis of oil-based drilling cuttings by microwave and electric heating. (15th December 2018) - Hou, Yingfei; Qi, Shengdong; You, Haipeng; Huang, Zhaoqi; Niu, Qingshan
Abstract: In this paper, the following questions were investigated: the proportion of mass loss, the mass fraction of oil, the structure, composition and ultimate analysis of solid residues and gas products. By comparing the treatment effect of using both microwave and electric as the source of heat to dispose the oil-based drilling cuttings (OBDC), the advantages of microwave heating treatment were demonstrated. Meanwhile, the composition of liquid products by microwave pyrolysis was analyzed. The results show that the microwave heating is better than electric heating and the former can promote the pyrolysis of petroleum hydrocarbons. The results of component analysis of the liquid products from OBDC by microwave pyrolysis show that C12∼C20 components pyrolyze at 500 °C. At the same time, a mass of C21∼C24 components volatilize. At the temperature above 500 °C, the thermal cracking reactions of >C25 components occur and a maximum content of paraffin in liquid products is obtained. As the temperature increases, the components obtained by pyrolysis become more and more complex. Highlights: In the removal of oil, microwave heating treatment is more effective. Microwave pyrolysis is excellent in inorganic matters decomposition. Microwave heating can promote the occurrence of the cracking reactions. The optimum temperature for producing oil with high aliphatic hydrocarbons is 500 °C.